Investigation of coupling loss caused by misalignment in optical fiber - Md Ashraful Haque; Mohd Azman Zakariya; Narinderjit Singh Sawaran Singh; Liton Chandra Paul; Md. Fatin Ishraque (Bulletin of Electrical Engineering and Informatics, 2023)
In a fiber optic communication system, optical fiber is used as a transmission medium consisting of a flexible filament that guides the optical signal to be transmitted from the transmitter to the receiver or vice versa. Like any other communication medium, the optical fiber cable faces some losses that can be caused by the material and length of the fiber. One of the main reasons for losses in optical communication systems is misalignment during the fiber to fiber joining process. This type of loss is also known as coupling loss, which is caused by an imperfect physical connection between two fibers. The coupling losses are most often caused by three misalignment issues: end gap displacement, lateral displacement, and angular displacement. The main goal of this article is to investigate coupling loss caused by misalignment in optical fiber using the Modicom 6 module. Before we can find a way to reduce the coupling losses in the fiber optic system, we need to have a concrete idea about the nature of coupling losses due to misalignment. An ideal fiber coupler should not lose light and should be insensitive to light dispersion.